The Effect of Prenatal Massage Towards Anxiety Level of Third Trimester Pregnant Women in The Work Area Of Cibeureum Public Health Center Tasikmalaya 2019 - Eva Ardianti; Sinar Pertiwi; Etin Rohmatin (Midwifery and Nursing Research, 2020)
Background: During pregnancy, most women experience psychological and emotional changes, it often comes up in the third trimester. Anxiety itself will have a negative impact on pregnant women to delivery, such as the fetal nervous and hindering growth, weakens the uterine muscle contraction, and others. One way to overcome anxiety in pregnancy with non-farmokologi method is prenatal massage.Methods: The study design used was pre-experimental research design with one group pretest posttest. Sampling in this research using purposive sampling technique with a sample size of 30 people. Pretest and posttest data retrieval using a measuring instrument HARS Scale (Hamilton Rating Scale for Anxiety). The data were analyzed using univariate and bivariate using Spearman Correlation Test.Result: Obtained results correlation value 0.769, it shows that the correlation is very strong with 0,000 ρvalue (ρvalue 0.05).Conclusion: Thus prenatal massage was effective to reduced the anxiety level of third trimester pregnant women